Peningkatan Kemampuan Menulis Esai Bagi Siswa SMAN 2 Tualang, Kecamatan Tualang - Eviza Riza; Alvi Puspita; TM Sum (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
The Science and Technology Program for the Community (IbM) which the team carried out was the Improvement of Essay Writing Ability for Students of SMA N 2 Tualang, Tualang District. The target to be achieved is the increased interest and ability of students in writing essays. As an additional value that is wanted to be obtained is the exploration of the locality of the area where this training is held through writing which will be produced by the students. The methods that the team used to achieve these targets were lectures, questions and answers and practice. The final result of the Essay Writing Training which is intended for SMA N 2 Tualang students is the emergence of students' interest in writing essays. The students wrote the essays in the second session of the activity after being provided with material about what essays are, types and functions along with essay examples. The participants' essays were collected at the end of the training activity.